2002
DOI: 10.1002/jmv.10214
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus (types 1 and 2) in the tear film in Sjogren's syndrome and HIV infection

Abstract: Evidence of Epstein-Barr virus (EBV) shedding in the saliva and tear film has been sought to explain the pathogenesis of the oral and ocular features of Sjogren's syndrome. Patients with human immunodeficiency virus (HIV) infection are purported to have a higher incidence of keratoconjunctivitis sicca. Twenty patients with definite Sjogren's syndrome (primary and secondary), 19 with HIV infection, and 15 normal controls were recruited and studied. Human herpes viruses (EBV 1 and 2, CMV, HZV, and HSV-1) in tear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
1
19
0
1
Order By: Relevance
“…In the eye, EBV has been reported to be associated with various diseases. [7][8][9][10][11][12][13][14][15][16] Interestingly, EBV genomic DNA and receptors are sometimes detected in normal ocular tissues, including the retinal epithelium and ocular fl uids, 5 under normal conditions. Usui and Sakai 12 reported high anti-VCA IgG in aqueous humor in three patients with EBV-associated uveitis without evidence of infectious mononucleosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the eye, EBV has been reported to be associated with various diseases. [7][8][9][10][11][12][13][14][15][16] Interestingly, EBV genomic DNA and receptors are sometimes detected in normal ocular tissues, including the retinal epithelium and ocular fl uids, 5 under normal conditions. Usui and Sakai 12 reported high anti-VCA IgG in aqueous humor in three patients with EBV-associated uveitis without evidence of infectious mononucleosis.…”
Section: Discussionmentioning
confidence: 99%
“…Among other etiologic factors for SjS, environmental factors, especially viral infections, are believed to be important. Several studies have shown viral involvement in subsets of SjS patients, which includes herpes simplex virus[32], Epstein-Barr virus [33], hepatitis C virus [34], human T-cell lymphocytic virus type 1 (HTLV-1) [35], and human endogenous retrovirus (HERV-11) [36]. Furthermore, because SjS usually occurs in females during peri-or post-menopause, hormone imbalance has also been suggested to trigger SjS with an altered androgen-estrogen ratio potentially giving rise to an increased risk of SjS development [37, 38].…”
Section: Sjogren’s Syndromementioning
confidence: 99%
“…Several viruses such as Epstein-Barr virus (EBV; types 1 and 2) [21, 22] and hepatitis C virus, retroviruses such as human T-cell lymphocytic virus type 1 (HTLV-1) [23], and endogenous retroviruses such as a HERV-K113 [24] have been found to be closely associated with the patients with pSjS and sSjS. Also, the incidence of keratoconjunctivitis sicca is increased in patients with exogenous retroviruses like immunodeficiency virus infection [25].…”
Section: General Introduction Of Sjsmentioning
confidence: 99%